Cost-effectiveness of a physiotherapist-led service for orthopaedic outpatients. (October 2014) - Comans, Tracy; Raymer, Maree; O'Leary, Shaun; Smith, David; Scuffham, Paul
Objective: Non-surgical treatment can be effective for many musculoskeletal conditions. Improving access to these options may improve the efficiency of hospitals. The Orthopaedic Physiotherapy Screening Clinic and Multidisciplinary Service offers early comprehensive assessment and coordinated, patient-centred care within a multidisciplinary framework. Our aim was to assess its cost-effectiveness compared with usual orthopaedic care. Methods: A Markov model was constructed to estimate the quality-adjusted life years and health care costs from the perspective of health care payers for outpatients with low back, knee or shoulder conditions compared to usual orthopaedic care. Data were obtained from a retrospective chart review, administrative sources, literature and expert opinion. The time frame was five years and all costs were reported in 2011 AUD. Results: Compared with usual orthopaedic care, the physiotherapist-led service costs an additional 495 per Quality Adjusted Life Year gained. The model remained cost-effective over a range of one-way sensitivity analyses. Conclusion: The physiotherapist-led service is likely to be highly cost-effective. Determining the optimal mix of hospital orthopaedic outpatient services may require more advanced modeling techniques to be applied.